Effect of novel polyethylene insert configurations on bone-implant micromotion and contact stresses in total ankle replacement prostheses: a finite element analysis - Xu, Zhi; Gong, Xiaonan; Hu, Zhengyuan; Bian, Ruixiang; Jin, Ying; Li, Yuwan (Frontiers in Bioengineering and Biotechnology, 2024)
Artificial ankle replacement (TAR) has been in existence for decades. TAR has preserved the function of the affected limb for osteoarthritis patients and has become an alternative to ankle arthrodesis. However, TAR has the disadvantage of a high revision rate, which has caused certain obstacles to the promotion of this technology.Considering that the main cause of TAR failure is prosthesis loosening, in order to prolong the TAR survival rate, the reduction of prosthesis micromotion becomes the focus of scholars. In our research this time, we followed the design idea of elastic optimization and developed 3 new inserts. In the new inserts, flexible materials are embedded in ordinary UHMWPE materials, which increases the elasticity of the inserts and can absorb more kinetic energy can reduce the bone-implant interface micromotion and joint surface contact stress, which provides a valuable reference for the development of a new generation of artificial ankle prosthesis. I hope this paper is suitable for Frontiers in Bioengineering and Biotechnology.We deeply appreciate your consideration of our manuscript, and we look forward to receiving comments from the reviewers. If you have any queries, please don't hesitate to contact me at the address below.